An overview on water quality, pollution sources, and associated ecological and human health concerns of the lake water of megacity: a case study on Dhaka city lakes in Bangladesh. Issue 3 (16th March 2023) - Uddin, Minhaz; Kormoker, Tapos; Siddique, Md. Abu Bakar; Billah, Md Masum; Rokonuzzaman, Md; Al Ragib, Abdullah; Proshad, Ram; Hossain, Md. Yeamin; Haque, Md. Kamrul; Ibrahim, Khalid A.; Idris, Abubakr M.
ABSTRACT: In Dhaka megacity (Bangladesh), lakes located in the most exclusive areas are considered crucial urban water bodies. However, these water sources are confronting a heavy load of organic and inorganic pollutants by anthropogenic activities and are being polluted continuously. In this review, 50 relevant published documents on the lake water of Dhaka megacity to highlight the overall water quality status and the potential ecological and human health risks associated with contaminations were studied. The retrieved documents were organized according to the relevant information and examined thoroughly. After a careful review, it was found that most of the lake water in Dhaka city is severely contaminated with heavy metals such as Pb, Cd, Cu, Zn, and Mn with a higher concentration of Pb and Cd than the guideline values for drinking and industrial uses. The physicochemical properties and microbial contamination with an elevated level of fecal coliforms in lake water indicate very poor water quality in all lakes. The EC and TDS in most of the lake water exceeded the standard limits with the highest EC value (4920 µS/cm) for Gulshan Lake. The indices-based water quality assessment revealed considerable heavy metal contamination in the lake's water. Few lakes are found at a minimal level of ecological risks. The assessments of health risk indicate lower non-cancer risk. Overall, it can be inferred that the lake water in the Dhaka megacity does not meet the requirements for domestic, drinking, fishing, and industrial uses. This review study will be helpful for the policymakers and environmentalists to know about the status and sources of pollution in the lake water in the megacity which in turn assist to take necessary actions to mitigate the pollution level from the studied lakes of Dhaka city, Bangladesh.